Can the free money transfer system application be considered a breakthrough in financial technology? - Rini Subekti; Elisabeth Ria Viana Praningtyas; Putu Ayu Anggya Agustina; Indah Setia Utami (Magister Akuntansi Universitas Pancasila, 2025)
Abstract Purpose:This study analyzes the customer experience of users of a free money transfer application in Indonesia. The application, developed by local innovators, enables users to transfer funds between bank accounts at no cost, representing an important contribution to the national fintech ecosystem. Methodology:The study employs Structural Equation Modeling–Partial Least Squares (SEM-PLS) as the analytical tool. Data were collected from users of the original Indonesia-based application designed to facilitate free money transfers. Findings:The results indicate that Ease of Use, Perceived Value, Customer Support, and Assurance do not significantly influence customer experience in the context of free money transfers. Unlike other fintech platforms, this application shows a different pattern of determinants. Speed and Perceived Firm Innovation emerge as the primary factors shaping customer experience. Implication:The findings may be used to guide the development of strategies to improve customer experience. Developers and policymakers should prioritize enhancements related to service speed and perceived innovativeness, as these represent the most influential factors for users of free-to-use money transfer applications. Originality:This study provides insight into customer experience in a uniquely Indonesian fintech application, offering an alternative perspective compared to studies focusing on commercial or fee-based fintech services. Keywords:Customer Experience; Fintech; Free Money Transfer